Death comes for the archbishop - Cather, Willa, 1873-1947. (New York : Vintage Books, 1990)
The literal and spiritual journey of two French priests who come to the American Southwest as missionaries in the mid-1800s.
Wilson's Senior High School.
Adult
Keywords: Allegories; Historical fiction; New Mexico -- History -- 1848- -- Fiction; New Mexico -- History -- Fiction; Allegories; Historical fiction